First report of an aegagropilous form of Cladophora prolifera (Cladophorales, Chlorophyta) from the lagoon of Strunjan (Gulf of Trieste, northern Adriatic) - BATTELLI, CLAUDIO; LELIAERT, FREDERIK (Mediterranean Marine Science, 2021)
The occurrence of unattached spherical (aegagropilous) populations of the green alga Cladophora prolifera in the marine lagoon of Strunjan (Gulf of Trieste) is reported. Species identification was based on molecular and morphological data, and the distribution, ecology and morphological features of the aegagropilous populations are described. The ball-shaped form of this species differs from the typical upright attached form found on open shores by the radial arrangement of the branches and the absence of cells and rhizoids with clear annular constrictions. The formation of the aegagropilous form of C. prolifera likely results from specific hydrodynamic conditions in the human-mediated environment of the marine lagoon, in combination with morphological development of the species. The Strunjan marine lagoon appears to be the only location in the Mediterranean Sea, or even worldwide, where aegagropilous forms of C. prolifera occur in large abundance. Based on the high associated biodiversity, we propose the inclusion of these populations to be considered in conservation management plans in the area.